FACTORS FOR FORMING CONSTITUTIONAL LITERACY OF PRIMARY SCHOOL STUDENTS - Jabborova O. M.; Ashurova D. R. (Galaxy International Interdisciplinary Research Journal, 2022)
The article analyzes the factors that shape the constitutional literacy of primary school students.